From an Eroding Model to Questioned Trade Relationships: the European Union and Sub-Saharan Africa - (:unkn) unknown (My University, 2014)
The paper analyses two key questions: the EU as a model of regional integration for developing countries (including Sub-Saharan Africa); and the EU as a trade partner. It argues that these two dimensions have been questioned since the mid-2000s and that this questioning stems from common interrogations on the credibility and the efficiency of the EU’s policy choices. The first step of the argument is that while the EU has represented a paradigmatic model of ‘developmental’ regional integration arrangements, the EU’s adherence to specific theoretical assumptions has eroded the credibility of its model (competition, fiscal discipline) as an optimal tool of growth and welfare. The second step of the argument is that these assumptions have influenced the theoretical framework and trade policies devised for developing countries, notably the Economic Partnership Agreements, which appear to be inefficient as tools for these countries’ growth. This theoretical framework has not only weakened the credibility of the EU as a model of a developmental regional integration, but also weakened the economic efficiency of its trade policies – and, in turn, the credibility for Sub-Saharan African countries of the assertion by the EU that its trade policies could be a tool of development.
Keywords: African Research